The Influence of Pearlite Present in the Microstructure of GX120MnCr13 Cast Steel on Wear Resistance - Barbara Kalandyk; Renata E. Zapała; Iwona Sulima; Piotr Furmańczyk; Justyna Kasińska (Archives of Foundry Engineering, 2023)
The article presents the results of metallographic and tribological tests on GX120MnCr13 cast steel that was previously subjected to heat treatment (including solution treatment from 1100°C and isothermal holding at 250, 400, and 600°C for 100 hours). The temperatures of the isothermal holding process were selected in order to reflect the possible working conditions of the cast elements that can be made of this cast steel. Wear tests were carried out under dry friction conditions using the ball-on-disc method using a ZrO2 ball as a counter-sample. The tests were carried out with a load of 5 N. The influence of the long-term isothermal holding process on the microstructure of the tested cast steel was analysed by light and scanning microscopy; however, abrasion marks were also examined using a confocal microscope. Based on the tests conducted, it was found that in the microstructures of the sample after solution treatment and samples that were held in isothermal condition at 250 and 400°C, the grain boundary areas were enriched in Mn and Cr compared to the areas inside the grains. Pearlite appeared in the sample that was heated (or held in isothermal holding) at 600°C; its share reached 41.6%. The presence of pearlite in the austenitic matrix increased the hardness to 351.4 HV 10. The hardness of the remaining tested samples was within a range of 221.8–229.1 HV 10. Increasing the hardness of the tested cast steel directly resulted in a reduction in the degree of wear as well as the volume, area, and width of the abrasion marks. A microscopic analysis of the wear marks showed that the dominant process of the abrasive wear of the tested friction pair was the detachment and displacement of the tested material through the indentation as a result of the cyclical impact of the counter-sample.